PENGARUH STRES KERJA DAN KONFLIK PERAN TERHADAP KEINGINAN BERPINDAH KARYAWAN DENGAN VARIABEL USIA MUDA SEBAGAI VARIABEL MODERATING (Studi Pada New Metro Hotel Semarang) - Aprilia, Fonny Kusmita; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this study was to examine the effect of job stress, role conflict and younger age on turnover intention. Independent variable in this study are job stress and role conflict.Turnover intention as dependent variable and younger age as moderating variable without neglecting older age variable. Methods of data analysis used in this research is regression analysis and sub-groups analysis.Methods of data collection in this study used a questionnaire with a sample of 80 employees of New Metro Hotel Semarang. The questionnaires were distributed by accidental sampling method or each individual is chosen randomly. Based on the regression analysis resulted that job stress has positive significant effect on turnover intention,and role conflict has positive and significant effect on turnover intention. Then based on the results of sub-group analysis suggest that the younger age moderate the relationship between job stress and turnover intention.